Photointerpretation as a Tool to Support the Creation of an Ontology for Dolmens - camara, A.; de Almeida, A.; Oliveira, J.; Silveira M, C. (XXVII Jornadas de Classificação e Análise de Dados – JOCLAD2020, 2020)
Photointerpretation as a Tool to Support the Creation of an Ontology for Dolmens